Ginger, Pepper and Curry Leaf Powder as Feed Additives in Broiler Diet - Moorthy, M.; Ravi, S.; Ravikuma, M.; Viswanathan, K.; Edwin, S.C. (International Journal of Poultry Science, 2009)
Two hundred and ten commercial, straight run day-old Vencobb broiler chicks belonging to single hatch were purchased from local hatchery, wing banded, weighed and randomly allotted into seven treatment groups with three replicates of ten chicks each. The chicks were reared in broiler cages in a gable roofed, open sided house. All the chicks were provided with uniform floor, feeder and waterer space and were reared under standard management conditions throughout the experimental period of six weeks. The treatments were T1-Control; T2-0.2% Ginger powder; T3-0.2% Pepper powder; T4-0.2% Curry leaf powder; T5-0.2% Ginger + 0.2% pepper; T6-0.2% Ginger + 0.2% Curry leaf powder and T7-0.2% Pepper + 0.2% Curry leaf powder. The mean body weight (g/bird) of broilers at 6 weeks of age fed with different inclusion levels of dried ginger, pepper and curry leaf powder differ significantly (p<0.05) among treatment groups at six weeks of age. The feed conversion ratio was significantly (p<0.01) superior in ginger-curry leaf (T6) and pepper-curry leaf powder (T7) fed groups compared to control. But the feed consumption did not differ significantly among treatment groups because of isocaloric and isonitrogenous diet. The mean return over feed cost of T2 and T5 was significantly (p<0.01) higher when compared to other treatment groups at sixth week of age. The carcass characteristics viz. pre-slaughter, New York dressed, eviscerated weights, ready-to-cook percentage, abdominal fat percentage and giblets weight did not differ significantly between the treatment groups fed different levels of dried ginger, pepper and curry leaf powder from 1-6 weeks of age.